Analisis Kebijakan Pendidikan Pesantren Modern: Integrasi Tradisi dan Modernisasi dalam Praktik Pembelajaran - Alfiyah Alfiyah; Nurul Fatimah; Jalaludin Jalaludin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Pondok pesantren (Islamic boarding schools) plays an important role in religious education and the character development of young generations in Indonesia. However, the times demand a transformation in pesantren education policy to integrate classical religious traditions with modern learning approaches. This study analyzes the policy of modern pesantren education focusing on the integration of tradition and modernization in learning practices. The research method employs a qualitative approach with content analysis techniques on scientific literature from 2020-2025 sourced from national and international journals and official policy documents from the Ministry of Education, Culture, Research, and Technology. Data analysis was conducted through content analysis techniques encompassing reduction, data presentation, and conclusion drawing. Findings show that government and pesantren policies have adopted an integrative approach, including strengthening the national curriculum, improving teacher competence through training, and applying information technology. Nonetheless, challenges such as cultural resistance to innovation and limitations of resources in traditional pesantren remain. In conclusion, the success of integration heavily depends on responsive policy synergy and strengthening of human resource capabilities.